An Unusual Case of Invasive Carcinoma with Squamous and Low-Grade Glandular Features Arising in a Giant Condyloma Acuminatum - Wong, Tina; Hussain, Nusrat; Chen, Frank (North American Journal of Medicine and Science, 2025)
We report an unusual case of invasive carcinoma with both squamous and glandular features arising in a giant anorectal condyloma acuminatum (GCA). The challenging part in rendering a definite diagnosis was the presence of a glandular component, its differentiation from other entities with similar histomorphology and low-grade human papilloma virus (HPV) expression in tumor cells. A 70-year-old woman presented with long standing symptoms of rectovaginal bleeding and recurrent perianal fistulas. She underwent an end-colostomy and later, an abdominoperineal resection. A large anorectal tumor was identified with associated invasive carcinoma showing both squamous and low-grade glandular features. The tumor recurred as pelvic mass within 6 months requiring chemoradiation therapy. The abdominoperineal resection specimen showed a large (> 5cm) verrucous mass at anorectal junction with an endophytic component invading vaginal fistulas and adjacent soft tissue. Histologically, the exophytic tumor had condylomatous proliferation with koilocytosis. The endophytic part showed invasive carcinoma with both squamous and low-grade glandular features. The glandular component was positive for CK7 and negative for CK20 and CDX-2, suggesting anal gland origin rather than a colorectal primary. High-risk HPV and p16 were both negative. In-situ hybridization (ISH) demonstrated low-grade HPV in tumor cells. GCA, also known as Buschke-Lowenstein tumor, occurs mostly in men and rarely transforms to invasive squamous cell carcinoma. Our female patient presented with recurring perianal fistulas and bleeding without detection of a condylomatous mass until after radical surgery. In addition, GCA associated with this particular pattern of squamous cell carcinoma (one with a glandular component) is exceedingly rare. The differential diagnoses included mucoepidermoid carcinoma, adenosquamous carcinoma and squamous cell carcinoma with mucinous microcystic pattern. The presence of low-risk HPV on ISH test, not only in the condyloma but also in the squamous and glandular cells of the invasive carcinoma, raises a question of its impact in tumor progression from condyloma to squamous as well as glandular invasive carcinoma. Besides being a diagnostic challenge, the clinical implication of this finding remains to be determined. [N A J Med Sci. 2025;18(1):013-017. DOI: 10.7156/najms.2025.1801013]